2010
DOI: 10.1007/s10165-010-0384-5
|View full text |Cite
|
Sign up to set email alerts
|

Reduction in serum levels of substance P in patients with rheumatoid arthritis by etanercept, a tumor necrosis factor inhibitor

Abstract: We determined the effects of etanercept on the serum concentrations of neuropeptides in RA patients. In a total of 11 patients who had been injected with etanercept, the serum levels of substance P, calcitonin gene-related peptide (CGRP), and gastrin-releasing peptide (GRP) were analyzed. Average levels of serum substance P were significantly reduced from 1.53 to 0.62 ng/ml after the injection of etanercept. In the CGRP and GRP analyses, these average levels dropped from 1.57 and 0.51 ng/ml to 0.44 and 0.04 ng… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 33 publications
0
4
0
1
Order By: Relevance
“…Independent reports have shown that mast cells, SP, IL-33, and TNF contribute to the inflammatory processes in these diseases (31,(47)(48)(49)(50)(51); for example, increased SP plasma levels (0.31 μg/L) that correlate with mast cell load have been reported in patients with mastocytosis (52). In addition, treatment with the TNF inhibitor etanercept has been shown to reduce serum SP levels in patients with rheumatoid arthritis (53). Our findings provide insight into how SP, IL-33, TNF, and mast cells may interact in these inflammatory diseases.…”
Section: Discussionmentioning
confidence: 99%
“…Independent reports have shown that mast cells, SP, IL-33, and TNF contribute to the inflammatory processes in these diseases (31,(47)(48)(49)(50)(51); for example, increased SP plasma levels (0.31 μg/L) that correlate with mast cell load have been reported in patients with mastocytosis (52). In addition, treatment with the TNF inhibitor etanercept has been shown to reduce serum SP levels in patients with rheumatoid arthritis (53). Our findings provide insight into how SP, IL-33, TNF, and mast cells may interact in these inflammatory diseases.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, reduction in CGRP tissue expression levels was seen in the dorsal root ganglia of rats injected with Entanercept (anti-TNFα treatment) (Horii et al, 2010). In both rats and humans with rheumatoid arthritis, CGRP and SP levels were reduced by 50% in the serum after treating with Etanercept (Origuchi et al, 2010). By contrast, TRPV1 activation via capsaicin and SA13353 (capsaicin analog) attenuated LPS-induced TNFα release in serum, and this effect was partially inhibited with CGRP antagonist treatment and in TRPV1 −/− or sensory denervated mice (Tsuji et al, 2009) suggesting a regulatory function for CGRP on TNFα i.e., CGRP is able to downregulate TNFα in vivo .…”
Section: Cgrp and Tnfα: A New Chaptermentioning
confidence: 99%
“…36 Notably, in diabetes mellitus and inflammatory disorders, the peripheral nervous system has been identified as a common cause of connective tissue healing malfunction and homeostasis. 13,71,74 …”
Section: Epidemiologymentioning
confidence: 99%